2014
DOI: 10.1002/marc.201400451
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Organization of Poly(ethylene oxide) on the Surface of Aqueous Salt Solutions

Abstract: It is demonstrated that stable Langmuir films of poly(ethylene oxide) (PEO) can be formed up to surface pressures of 30 mN m(-1) when potassium carbonate K2CO3 is added to the aqueous subphase. Generally, PEO homopolymer cannot stay on the water surface at a surface pressure ≥10 mN m(-1) due to its high water solubility. To prepare stable monolayer films, PEO can be modified with hydrophobic moieties. However, by exploiting the salting out effect by adding certain salts (K2CO3 or MgSO4) into the aqueous subpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…This agrees with reports on PEO monolayers that showed an increase in surface concentration of PEO when a salt was added to the subphase [51]. Furthermore, a plateau region is observed in the corresponding Langmuir isotherm on a 2 M and a 4 M K 2 CO 3 aqueous subphase [25]. During this transition, the formation of crystalline structures within the monolayer could be followed by BAM as demonstrated in Fig.…”
Section: Polymers With Peosupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with reports on PEO monolayers that showed an increase in surface concentration of PEO when a salt was added to the subphase [51]. Furthermore, a plateau region is observed in the corresponding Langmuir isotherm on a 2 M and a 4 M K 2 CO 3 aqueous subphase [25]. During this transition, the formation of crystalline structures within the monolayer could be followed by BAM as demonstrated in Fig.…”
Section: Polymers With Peosupporting
confidence: 91%
“…Recently, it has been demonstrated that PEO is able to crystallize on certain aqueous salt solutions [25]. The selection of suitable salts follows the so-called Hofmeister series [26,27].…”
Section: Polymers With Peomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the PEG-400 is known as an hydrophilic polymer but it can display a "surfactant-like" behavior as it decreases the surface tension of water. [40][41][42][43][44][45][46][47][48] These observations may also explain the differences observed in the obtained porous structures, and how a classical surfactant like F-127 can stabilize for a longer time smaller droplets, delaying the coalescence, while the PEG-400 has a weaker ability to stabilize the droplets. Contact angles measurements (on PTFE substrate) have also been done using water.…”
Section: Surface Tension Measurements and Monitoring Of The Droplet Evaporation With The Goniometermentioning
confidence: 99%
“…A lot of studies are relative to the salt influence on the behavior of PEG or block copolymers. [45][46][47][48][49][50][51][52][53][54][55] PEG tends to form complex with salts and these complex are considered to have cations trapped within the PEO helices. Salts decrease the cloud point of PEG containing polymers and favorise their phase separation process.…”
Section: Surface Tension Measurements and Monitoring Of The Droplet Evaporation With The Goniometermentioning
confidence: 99%